2017
DOI: 10.1016/s0140-6736(17)30575-5
|View full text |Cite
|
Sign up to set email alerts
|

The safety, immunogenicity, and acceptability of inactivated influenza vaccine delivered by microneedle patch (TIV-MNP 2015): a randomised, partly blinded, placebo-controlled, phase 1 trial

Abstract: Background Microneedle patches provide an alternative to conventional needle-and-syringe immunization, and potentially offer improved immunogenicity, simplicity, cost-effectiveness, acceptability and safety. We describe safety, immunogenicity and acceptability of the first-in-human study on single, dissolvable microneedle patch vaccination against influenza. Methods The TIV-MNP 2015 study was a phase 1, partially blinded, placebo-controlled, randomized clinical trial conducted at Emory University that enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
283
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(314 citation statements)
references
References 23 publications
(30 reference statements)
10
283
1
1
Order By: Relevance
“…Most studies utilize commercial available hollow MN infusion systems, and a few cases have investigated the effectiveness of using polymeric MN for protein drug delivery. For example, a Phase I study investigating the safety and immunogenicity of the dissolvable MN for the delivery of H1N1, H3N2 and B seasonal influenza virus vaccine strains has been published (ClinicalTrials.gov identifier: NCT02438423) [185]. A coated transdermal MN delivery system has been completed in phase II clinical study for the systemic delivery of a parathyroid hormone-related protein (ClinicalTrials.gov identifier: NCT01674621).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies utilize commercial available hollow MN infusion systems, and a few cases have investigated the effectiveness of using polymeric MN for protein drug delivery. For example, a Phase I study investigating the safety and immunogenicity of the dissolvable MN for the delivery of H1N1, H3N2 and B seasonal influenza virus vaccine strains has been published (ClinicalTrials.gov identifier: NCT02438423) [185]. A coated transdermal MN delivery system has been completed in phase II clinical study for the systemic delivery of a parathyroid hormone-related protein (ClinicalTrials.gov identifier: NCT01674621).…”
Section: Discussionmentioning
confidence: 99%
“…A new first-in-human trial using dissolvable microneedle patches for influenza vaccination revealed the vaccines were stable for more than 1 year and generated titers similar to those of existing injectable vaccines even when self-administered by recipients [4345]. Such advances could transform the way vaccines are delivered, as well as the accessibility of effective formulations in developing regions.…”
Section: Biomaterials Can Improve Immunogenicity and Durability Of Vamentioning
confidence: 99%
“…Although studies have shown that solid microneedles future science group www.futuremedicine.com can enhance the permeability of drugs for up to 5 h, there is a lack of data on how quickly the pores created by the device will close which could increase the risk of transfer of infection through the skin. However, research published by a research team at Emory University, Atlanta, from a clinical trial looking at the use of dissolvable microneedle patches for influenza vaccination showed the approach was well tolerated and generated effective antibody responses [15]. About 70% of patch recipients said that they preferred this approach over other methods of delivery, so it is highly likely that the concerns mentioned above will be addressed and microneedle devices will be seen in the market in the next few years.…”
Section: Patents and Novel Technologymentioning
confidence: 99%